2015
DOI: 10.1016/j.jocd.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Calibration Study of the GE-Lunar iDXA and Prodigy for the Assessment of Lumbar Spine and Total Hip Bone Parameters via Three Statistical Methods

Abstract: This study assessed agreement between the GE Lunar iDXA and Prodigy densitometers for bone measurements and used 3 statistical methods to derive cross-calibration equations: linear regression, the Deming method, and multivariate analysis. Compatibility of machines for the measurements of bone mineral density, bone mineral content, and bone area also was explored. Eighty-five adults, age: 45.5 (SD 12.8) years; body mass index: 25.6 (SD 3.7) kg.m −2were measured once at the lumbar spine: L1-L4 and total hip on e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 21 publications
2
16
2
4
Order By: Relevance
“…Thus, compared to previous results [ 4 , 6 , 7 ], the discrepancy could be 2.7%, 2.5%, and 1.1% at spine [ 4 ], femoral neck [ 4 ], and total hip [ 7 ], respectively. Importantly, linear correction equations between iDXA and Prodigy, as derived in these previous cross-calibration studies [ 4 , 6 , 7 ] and implemented in the present study, would have increased the disagreement, especially at the femoral neck, the total hip, and the lumbar spine ROIs, between our two DXA devices. Furthermore, no significant correlations were observed between BMD Prodigy and BMD iDXA differences and mean BMD values of the two devices in femoral neck, total hip, and lumbar spine ROIs [ 4 ].…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Thus, compared to previous results [ 4 , 6 , 7 ], the discrepancy could be 2.7%, 2.5%, and 1.1% at spine [ 4 ], femoral neck [ 4 ], and total hip [ 7 ], respectively. Importantly, linear correction equations between iDXA and Prodigy, as derived in these previous cross-calibration studies [ 4 , 6 , 7 ] and implemented in the present study, would have increased the disagreement, especially at the femoral neck, the total hip, and the lumbar spine ROIs, between our two DXA devices. Furthermore, no significant correlations were observed between BMD Prodigy and BMD iDXA differences and mean BMD values of the two devices in femoral neck, total hip, and lumbar spine ROIs [ 4 ].…”
Section: Discussioncontrasting
confidence: 66%
“…In the present study, iDXA measured BMD values at the lumbar spine (L2–L4), femoral neck, and total hip were higher than those measured with Prodigy (i.e., 1.5%, 0.5%, and 0.9%, resp.). In contrast, previous studies have reported that BMD iDXA values were lower than BMD Prodigy values at the lumbar spine (ranging from −0.25% to −1.2%), femoral neck (ranging from −0.7% to −2.0%), and total hip (ranging from −0.1% to −0.2%) ROIs [ 4 , 6 , 7 ]. As an exception Choi et al measured BMD iDXA values to be 0.3% higher than BMD Prodigy values at the total hip ROI [ 4 ].…”
Section: Discussionmentioning
confidence: 71%
“…При моделировании ПжК и выполнении ручной коррекции выделения площади lSc = 0,0101×1,96 = 0,019 г/см 2 . эти данные сопоставимы, хотя несколько выше результатов многократных измерений lSc по рекомендациям IScD, выполненным на iDxa (lSc = 0,014 г/см 2 ) [11]. Фантом РСК ФК2 перспективен для разработки методики оценки lSc без сканирования пациентов, которое актуально в условиях отсутствия нормативно-правовой базы для подобного рода исследований (без медицинских показаний), т.к.…”
Section: Discussionunclassified
“…Применение в разработанном фантоме двух вариантов модификации (с моделированием ПжК и без) обеспечивает проведение кросс-калибровки исследований на разных аппаратах, учитывая значение ИМТ пациентов. например, результаты сканирования фантомов разных типов, включая eSP, продемонстрировали идентичность измерений МПК для двух сканеров lunar iDxa и Prodigy, однако последующие исследования пациентов с разными ИМТ выявили различия в измерениях МПК, что позволило уточнить параметры кросс-калибровки [11]. Продемонстрированное в нашей работе влияние жировой ткани, приводящее к относительному повышению измеренной МПК, согласуется с результатами клинических данных, полученных при наблюдении пациентов с ожирением после бариатрического лечения [23].…”
Section: Discussionunclassified
See 1 more Smart Citation